1998
DOI: 10.1346/ccmn.1998.0460409
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Transformation of Bioweathered Granitic Biotite, Studied by HRTEM: Evidence for a New Pathway in Lichen Activity

Abstract: The question of whether clay minerals can be biogenically transformed as a result of lichen activity at the lichen-rock interface remains unresolved. We applied several microscopical and analytical techniques--scanning electron microscopy-back-scattered electron (SEM-BSE), energy dispersive spectroscopy (EDS) and high-resolution transmission electron microscopy (HRTEM)--in an attempt to address this issue. Unaffected granitic biotite and bioweathered material from the granitic biotite and Parmelia conspersa li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 33 publications
4
21
0
2
Order By: Relevance
“…Pioneer work by Wilson et al (1981) reported the complete Mg depletion of chrysotile colonized by Lecanora atra, yielding amorphous silica as deterioration product. Incongruent ion depletion was also previously reported for other phyllosilicates, as biotite and muscovite, contacted by lichen thalli ( Ascaso and Wierzchos, 1996;Prieto et al, 1997;Wierzchos and Ascaso, 1998).…”
Section: Chrysotile In Pure and Mixed Veinssupporting
confidence: 71%
“…Pioneer work by Wilson et al (1981) reported the complete Mg depletion of chrysotile colonized by Lecanora atra, yielding amorphous silica as deterioration product. Incongruent ion depletion was also previously reported for other phyllosilicates, as biotite and muscovite, contacted by lichen thalli ( Ascaso and Wierzchos, 1996;Prieto et al, 1997;Wierzchos and Ascaso, 1998).…”
Section: Chrysotile In Pure and Mixed Veinssupporting
confidence: 71%
“…In addition, no chemical alteration of the biotite underneath the cyanobacterial filament was detected via EDX ( Figure 5) or EELS (Figure 6) within the resolution limitations described above. In other studies, weathering of biotite by lichen has been shown to result in a depletion of potassium (Wierzchos and Ascaso, 1998), and the study by Bonneville et al (2009) showed depletion of potassium, iron, aluminium and magnesium. The potential detection of iron depletion in the surface 5 nm of the biotite studied here ( Figure 5) is below the resolution limits measured here (~15 nm for EDX linescan and ~6-7 nm for EF-TEM) and could also, arguably, be described as relatively insignificant in terms of the bioweathering of biotite observed in incubation experiments with other microorganisms (Bonneville et al, 2009 and2011).…”
Section: The Cell-mineral Interfacementioning
confidence: 83%
“…In general, the presence of microorganisms-such as algae, lichen and fungi-indicates higher humidity, which may enhance deterioration processes (Wihr 1986). Biological deterioration of microorganisms can be divided into biophysical and biochemical deterioration processes (Adamo and Violante 2000;Dornieden and Gorbushina 2000;Pinna and Salvadori 2000;Wierzchos and Ascaso 1998). The extent of biological weathering is dependent on qualitative and quantitative distribution of microorganisms and their metabolic products.…”
Section: Introductionmentioning
confidence: 99%